Assisted suicide and the discrimination argument: Can people with mental illness fulfill beneficence- and autonomy-based eligibility criteria? - Braun, Esther (Bioethics, 2024)
According to the “discrimination argument,” it would be discriminatory and hence impermissible to categorically exclude people with mental illness (PMI) from access to assisted suicide (AS) if AS is accessible to people with somatic illnesses. In objection to this, it could be argued that excluding PMI is not discriminatory, but rather based on their inability to meet certain eligibility criteria for AS. Which criteria are deemed necessary depends on the approach taken to justifying AS. In this article, we describe two distinct ethical approaches to justifying AS and the eligibility criteria they entail and examine whether PMI can fulfill these criteria. A widespread “joint” approach based on beneficence and autonomy assumes that AS is justified when it alleviates the severe and irremediable suffering of a person who autonomously requests AS. An alternative, exclusively autonomy-based approach assumes that providing AS is justified when a person's request is autonomous, regardless of whether AS is in her best interests. The latter approach underlies an important judgment of the German Federal Constitutional Court from 2020. We argue that PMI can in principle fulfill both beneficence- and autonomy-based eligibility criteria for AS, and that a blanket exclusion of all PMI from AS is thus discriminatory on either approach. However, depending on which approach is taken, there are differences regarding the subgroups of PMI that would be eligible for AS. Whether the exclusion of specific PMI is discriminatory therefore depends on how we understand and justify AS.